2014
DOI: 10.1371/journal.pone.0095723
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviruses Using the Cancer Marker EphA2 as a Receptor In Vitro and In Vivo by Genetic Ligand Insertion into Different Capsid Scaffolds

Abstract: Adenoviral gene therapy and oncolysis would critically benefit from targeted cell entry by genetically modified capsids. This requires both the ablation of native adenovirus tropism and the identification of ligands that remain functional in virus context. Here, we establish cell type-specific entry of HAdV-5-based vectors by genetic ligand insertion into a chimeric fiber with shaft and knob domains of the short HAdV-41 fiber (Ad5T/41sSK). This fiber format was reported to ablate transduction in vitro and biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Adenoviruses show promise as vectors for gene therapy and vaccination, and as oncolytic agents [113-115]. However, safe use of adenoviruses in the clinic requires engineering their capsid proteins to redirect their tropism from healthy cells to specific diseased cells of interest, for example by genetic insertion of short peptide ligands targeting specific cell surface receptors.…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviruses show promise as vectors for gene therapy and vaccination, and as oncolytic agents [113-115]. However, safe use of adenoviruses in the clinic requires engineering their capsid proteins to redirect their tropism from healthy cells to specific diseased cells of interest, for example by genetic insertion of short peptide ligands targeting specific cell surface receptors.…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
“…The YSA peptide, which can be encoded by the adenovirus genome because it contains only natural amino acids and which can also promote adenovirus internalization through EphA2 activation [51], shows particular promise for adenoviral transduction of EphA2-positive cancer cells. Several studies with YSA-redirected adenoviruses have demonstrated efficient EphA2-dependent transduction of endothelial, osteosarcoma and pancreatic cancer cells in culture as well as of ex vivo slices from patient-derived pancreatic tumors and melanoma metastases [98, 113, 116, 117]. Successful in vivo transduction of pancreatic cancer and melanoma xenografts in the mouse was also observed after intratumor adenovirus injection but not yet through systemic adenovirus administration, which represents the next goal.…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
“…Although AdC7 has some advantages over AdHu5 as oncolytic viruses, AdC7 without modification could not address the AdHu5 drawback of nonselectivity in infecting target cells. This problem might be overcame by attempts to genetically alter the fiber protein [ 30 ] or to insert some peptides into the hexon region [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudotyping of the fiber capsid with fiber knob domains of other serotypes, such as serotypes 3 or 35, is yet another way of directing viral oncolysis towards desmoglein-2 expressing [ 94 ] or CD46-expressing cancer cells, respectively [ 95 ]. Likewise, insertion of targeting peptides in the fiber knob domain can enhance tumor specificity of replication competent adenoviral vectors [ 96 ] [ 97 ].…”
Section: Viral-derived Vectorsmentioning
confidence: 99%